2000
DOI: 10.1523/jneurosci.20-19-07149.2000
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor Supports Normal Development of Photoreceptor Neurons and Opsin Expression after Retinal Pigment Epithelium Removal

Abstract: Dysfunction of the retinal pigment epithelium (RPE), its loss, or separation from the underlying neural retina results in severe photoreceptor degeneration. Pigment epithelium-derived factor (PEDF) is a glycoprotein with reported neuroprotective and differentiation properties that is secreted in abundance by RPE cells. The "pooling" of PEDF within the interphotoreceptor matrix places this molecule in a prime physical location to affect the underlying neural retina. The purpose of this study was to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 51 publications
1
85
0
Order By: Relevance
“…It is anticipated that LBD peptides will prove to be useful for probing the involvement of PEDF-R in other PEDF-mediated cellular effects. For example, P1 blocked PEDF-mediated axon growth on primary retinal ganglion cells, 4 supporting the idea that PEDF specifically interacts with PEDF-R to induce neurotrophic effects.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…It is anticipated that LBD peptides will prove to be useful for probing the involvement of PEDF-R in other PEDF-mediated cellular effects. For example, P1 blocked PEDF-mediated axon growth on primary retinal ganglion cells, 4 supporting the idea that PEDF specifically interacts with PEDF-R to induce neurotrophic effects.…”
mentioning
confidence: 55%
“…In both systems, the Bcl-2 signal induced nuclear translocation of apoptosis-inducing factor, a caspase-independent apoptosis inducer (40). Although these studies did not report a receptor for PEDF signaling, our findings demonstrate that PEDF-R can mediate these effects, 4 Y. Yin, personal communication. FIGURE 8.…”
mentioning
confidence: 60%
“…Collectively, Trx released from the RPE cells contributes to the cytoprotection of photoreceptor cells by eliminating oxidative stress. The RPE releases several neurotrophic factors such as nerve growth factor (NGF), brain-derived growth factor, neurotrophin-3 (Ishida et al, 1997), and pigment epitheliumderived factor (Jablonski et al, 2000). These neurotrophic factors confer cytoprotection against light-induced photoreceptor cell damage (LaVail et al, 1992;Cao et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in several cases the pigmented part of the implant had detached itself from the transdifferentiated part so that the implant resembled a small ''inverted eye'' with the ONL facing the inner cavity of the implant. Since it has been demonstrated that the RPE secretes the pigment epithelium-derived factor (PEDF) that exerts a very powerful morphogenetic effect on photoreceptors of the embryonic eye (Jablonski et al, 2000;Karakousis et al, 2001), the differentiation of the ONL in our polarized implants could have been promoted by the PEDF produced by the pigmented part of the implant and accumulated in the implant's inner cavity. Moreover, the differentiation of the new-forming laminar retina could also have been promoted by locally acting factors.…”
Section: Discussionmentioning
confidence: 99%